Bilişim toplumunda entelektüel sermayenin unsurlarının belirlenmesi için kriterler ve bilişim firmalarında yapılan bir inceleme - Küçük, Yeliz (My University, 2005)
Son yıllarda yaşanan bilgi ve iletişim teknolojilerindeki gelişmeler, bilginin değerinin hızla artmasını sağlamıştır. Organizasyonlarda bilgi, maddi varlıklardan daha önemli hale gelmiştir. Bilişim toplumunda bilgiyi üretebilen ve kullanarak geliştiren organizasyonlar rekabet avantajı kazanmıştır. Bu çalışma ile bilişim toplumunda entelektüel sermayenin unsurlarının belirlenmesi için kriterler ortaya konularak, söz konusu kriterlerin belirlenen bilişim firmalarındaki varlığı incelenmiştir.

THE CRITERIONS FOR THE DETERMINATION OF THE COMPONENTS OF THE INTELLECTUAL CAPITAL IN AN INFORMATION SOCIETY AND A RESEARCH ABOUT THE FIRMS AT INFORMATICS SECTOR The developments in the information and communication technologies that are experienced in the last years have provided a rapid increase in the value of the information. In organizations, the information has become more important than material beings. The organizations, that can produce information and improve it by using at the information society, have gained the advantage of competition. With this work, by revealing the criterions for the determination of the elements of the intellectual capital within information society, the presence of these mentioned criterions at the specified informatics sector firms are examined.
Keywords: Bilişim; İletişim; Toplum bilimleri; Toplumsal etkileşim